Trójwymiarowe modelowanie wartości parametrów złożowych metodą krigingu zwyczajnego 3D - Mucha, Jacek; Wasilewska-Błaszczyk, Monika (Wydawnictwa AGH, 2009)
The principles of 3D modelling of deposit parameters by means of geostatistical procedure of 3D ordinary kriging were outlined. The use of the procedure was illustrated by example of Cu content assessment in exploitation blocks in a one of the deposits Cu-Ag from Fore-Sudetic Monocline. A new classification of accuracy of mean Cu content estimation in exploitation blocks was proposed.
3D modelling of deposit parameters using ordinary kriging
Geologia
Keywords: 3D modelling; semivariograms; 3D kriging; Cu deposits; modelowanie 3D; semiwariogramy; kriging 3D; złoża Cu